“Hagekorset over radioen”: : Statsradiofonien under besættelsen, 1940-1945 - Batikha, Joseph (Arbejderhistorie, 2023)
this media history article seeks to investigate the events that transpired with the danish state radio during 1940-1945, the years of German occupation. after 9 april 1940, the radio was no longer only in the hands of Danish radio oﬃcials as it was constrained to comply with the Danish government’s policy of cooperation with the Germans. The article examines how the state radio actively contributed to the creation of post-war supporting narratives about itself. in several works, anniversary publications, and chronicles after 1945, the radio described its own role during the occupation. These publications, which are the empirical starting point of the article, were formulated by actors who had themselves borne a great deal of responsibility for the policy of negotiation with the germans. The article concludes that the Danish state radio wrote itself into a consensus narrative, in which the radio maintained a national and democratic defense against the germans throughout the occupation. Through these narratives, the Danish radio was able to claim a larger social role in the post-war period.